2022
DOI: 10.1214/21-aoas1502
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of replication success based on relative effect size

Abstract: Replication studies are increasingly conducted in order to confirm original findings. However, there is no established standard how to assess replication success, and, in practice, many different approaches are used. The purpose of this paper is to refine and extend a recently proposed reverse-Bayes approach for the analysis of replication studies. We show how this method is directly related to the relative effect size, the ratio of the replication to the original effect estimate. This perspective leads to a n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 36 publications
0
40
1
Order By: Relevance
“…The sceptical p-value also penalises the case when the replication effect estimate shrinks as compared to the original one since it monotonically increases with decreasing relative effect estimate d (Held, 2020, section 3.1). Held et al (2022b) showed that replication success based on p S ≀ đ›Œ S is achieved when…”
Section: The Sceptical P-valuementioning
confidence: 99%
See 4 more Smart Citations
“…The sceptical p-value also penalises the case when the replication effect estimate shrinks as compared to the original one since it monotonically increases with decreasing relative effect estimate d (Held, 2020, section 3.1). Held et al (2022b) showed that replication success based on p S ≀ đ›Œ S is achieved when…”
Section: The Sceptical P-valuementioning
confidence: 99%
“…For example, when z o = 2, đ›Œ = 0.025, and c = 2, the replication effect estimate needs to be d = 4.87 times larger than the original one. Therefore, Held et al (2022b) used Equation ( 14 The bottom-right plot in Figure 4 shows the success region for the recalibrated sceptical p-value. We see that increasing the precision of the replication study lowers the required minimum relative effect estimate d min as for all other methods.…”
Section: The Sceptical P-valuementioning
confidence: 99%
See 3 more Smart Citations